Два типа рудной минерализации золото-полиметаллического рудопроявления Балки Широкой (Среднее Приднепровье) - Фомин, Ю.А.; Демихов, Ю.Н.; Лазаренко, Е. Е.; Блажко, В.И. (Видавничий дім "Академперіодика" НАН України, 2007)
Quartz-polymetal mineralization in volcanic metasomatites (propylites) (1) was transformed by a metamorphism (530–450 ◦ С) which destroyed the ﬂuid inclusion system and disturbed the sulfur isotope equilibrium in sulﬁdes. The Au−Ag−Pb−Zn ores in beresites (2) were formed by the post metamorphic activity with generation of the epithermal regressive sulﬁde-bearing system close to the equilibrium temperature range 420–110 ◦ С. In view of the difference in tendencies for the 34 S content to vary in ore systems, the inversion of ore-forming conditions from the oxidizing (1) to restoring (2) ones took place.